Spectrophotometric Determination of Trace Quantities of Pure Atropine and Pharmaceutical Preparations with SbI42− Ion - Riyadh Hasan Mohammed Ali; Bashar Mudhaffar Abdullah; Rasha Ismail Ahmed (Universitas Gadjah Mada, 2023)
This study aims to estimate a simple, rapid and sensitive method for a trace amount of atropine (ATR) in medicinal compounds. Two approaches were followed to accomplish this aim, i.e., spectrophotometric determination of pure ATR and pharmaceutical preparations using SbI42− ion as a new reagent. The procedure involves the implementation of an ion-association complex with this alkaloid. The resulting complex was extracted and detected spectrophotometrically at 492 nm. Appropriate parameters were investigated, including the ion SbI42− concentration and the pH value of the complex formation. Using chloroform to extract the complex, taking into consideration extraction time and volume of solvent used. The calibration graph is linear in the ranges of 0.5–5.0 × 10−3 M. Precision, accuracy, detection limit, and RSD %, as well as relative standard deviation (n = 5), were calculated. The test sensitivity was 0.013 µg cm−2. Several interference additives were studied by investigating the effect of equal and duplicate quantities of some common excipients on selectivity, such as starch, glucose, lactose, glycerin, and talc. The molar ratio of the SbI42−_ATR was determined. The amount of ATR in the pharmaceutical tablets and eye drop preparation was calculated using Erel at ratios of 2.24 and 2.75%, respectively.